(untitled) (Indo-American Journal of Life Sciences and Biotechnology, 2023)
These days, UV-visible spectroscopy is widely used as a quick, easy, accurate, and very accurate technique for quantitative estimation. The fundamental idea behind this method is that the analyte concentration is directly correlated with the quantity of light absorbed. While multi-component analysis may be used on any degree of spectral overlap as long as two or more spectra are not precisely the same, the simultaneous equation is only useful for estimating medications whose spectra overlap appropriately. Before a medicine is introduced to the market, quantitative assessment is required since a formulation with a higher concentration may create toxicity issues, while one with a lower concentration may not work as intended.